2010
DOI: 10.1177/1352458510376178
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a patient self-assessed questionnaire on satisfaction with communication of the multiple sclerosis diagnosis

Abstract: COSM-R is a brief, easy-to-interpret MS-specific questionnaire for use as a health care indicator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 40 publications
1
26
0
2
Order By: Relevance
“…The first three items of section 1 (items 6a, 6b and 6c) had the most missing responses, with three times more missing responses for items 6b and 6c than 6a. These findings, on a larger sample, are consistent with those of the original publication, 14 and suggest that PwMS tended to interpret item 6a as the only item, and to skip the next two. For the remaining COSM-R items, the missing data rate was around 1%.…”
Section: Response Ratesupporting
confidence: 90%
See 1 more Smart Citation
“…The first three items of section 1 (items 6a, 6b and 6c) had the most missing responses, with three times more missing responses for items 6b and 6c than 6a. These findings, on a larger sample, are consistent with those of the original publication, 14 and suggest that PwMS tended to interpret item 6a as the only item, and to skip the next two. For the remaining COSM-R items, the missing data rate was around 1%.…”
Section: Response Ratesupporting
confidence: 90%
“…Thus in the example, the vertical line at 1 logit (corresponding to a raw score of 30) crosses response 3 (fourth band) for items 10,19,14,17,15,16, and response 2 (third band) for the remaining items. If for an individual with raw score of 30, one or more item responses were outside those illustrated, it would indicate an inconsistent response profile.…”
Section: Reliability and Validitymentioning
confidence: 98%
“…Patients were randomly assigned to MS diagnosis disclosure (current practice at the center; n = 60) or current practice plus the information aid (n = 60). The primary composite endpoint were scores in the highest tertile of MS knowledge [12] and satisfaction with care [25] questionnaires, one and six months after diagnosis disclosure. Other endpoints were: safety, between-group differences in questionnaire scores, treatment adherence, extra contacts/consultations, switching of care center, changes in Hospital Anxiety and Depression Scale (HADS), and CPS scores.…”
Section: Sims Trial -Structured Information Interview In People With mentioning
confidence: 99%
“…Our previous studies have shown that MS patients claim active roles, appreciate comprehensive information, are able to handle risk calculation tasks16 17 and can cope with uncertainty 18. Solari et al 19 have studied comprehensive information with additional physician-based counselling directly after an MS diagnosis, resulting in increased knowledge and satisfaction without negative side effects, but this intervention was physician-based, did not apply evidence-based patient information and did not focus early DMD decision making. In summary, there is a clear need for better patient information and decision support, especially in the diagnostic process and the early stages of MS.…”
Section: Introductionmentioning
confidence: 99%